Characteristics Of Blood Viscosity And Parameters Affecting It (Eurasian Research Bulletin, 2025)
Blood viscosityisan importantbiophysical parameterdeterminingthe efficiencyof blood circulation and oxygen transport in the body.It depends on blood composition, red blood cell properties,temperature, and blood flow velocity. Changes in viscosity play a key role in clinical diagnostics and the functional state of the cardiovascular system.